The human resource focus in the 10th Malaysia Plan: Is talent management corp adequate? - Sharif, Mohmad Yazam; Teng, Jane Yang Fang; Md Ali, Azham (2011)
The aim of this paper is to present an analysis of the government’s growth machinery called ‘Talent Corporation’ (TC). Based on the idealism of ‘talent management’ in organizations, it was envisaged that managing Malaysian talented professionals should be done and should be done systematically.Talent Corp or TC was set up as one of the government tools in the 10th Malaysia Plan (2011 – 2015). The prime focus of the 10th Malaysia Plan (10MP) is human resource or human capital development so as to ensure that the long‐term goals of Malaysia’s Vision 2020 will be met. With the establishment of TC, the government hopes to attract foreign professionals and professionally qualified Malaysians working overseas to come back and work in Malaysia. At the same time, the government also wants TC to find ways to retain Malaysian talented professionals to remain in Malaysia. The question is whether Talent Corp is adequate to play this crucial role.Interviews were conducted among 15 HR academics to determine whether they viewed the attention given to Talent Corp is justified.